Cervical intradural disc herniation: a new diagnostic clue based on MRI T2 hyperintensity and intraoperative increased water content in the intervertebral disc—a case report and mechanistic insights - Guo, Guodong; Shi, Xiaohui; Qiu, Yang; Gao, Daokuan; Fang, Peng; Ma, Huijuan; Liu, Gang (Frontiers in Surgery, 2025)
BackgroundCervical intradural disc herniation (CIDH) is a rare spinal condition characterized by herniation of nucleus pulposus through the dura mater into the subarachnoid space, resulting in spinal cord or nerve root compression. Its rarity and nonspecific imaging features make preoperative diagnosis particularly challenging.Case presentationWe report a 55-year-old man with sudden-onset left-sided limb weakness and inability to walk, without prior trauma. Neurological examination revealed Brown-Séquard syndrome, with ipsilateral motor deficits and contralateral sensory loss. Sagittal T2-weighted MRI demonstrated marked hyperintensity at the C4/5 intervertebral disc compared to adjacent levels. Intraoperatively, the disc material exhibited visibly increased water content compared to typically desiccated degenerative discs. A small amount of clear fluid was noted near the posterior longitudinal ligament. Further exploration revealed a ventral dural tear with herniated disc fragments within the subarachnoid space, confirmed histologically as CIDH. The patient underwent anterior cervical corpectomy and fusion with dural repair, resulting in neurological recovery. At one-year follow-up, only mild residual weakness in the left hand remained.ConclusionThis case underscores T2 hyperintensity and intraoperative detection of disc tissue with increased water content as potential indicators of CIDH in acute cervical myelopathy. Recognizing these features may support earlier diagnosis, guide surgical planning, and reduce complications such as cerebrospinal fluid leakage.